Optimal operation of multi‐vector energy storage systems with fuel cell cars for cost reduction. Issue 6 (11th November 2020) - Tang, Can; Gu, Chenghong; Li, Junlong; Dong, Shufeng
Abstract : Combined borehole (BH) heat storage systems, batteries and power‐to‐gas system have the potential to shift load, reduce carbon emissions, provide hydrogen for fuel cell cars and save energy costs for end customers on an extended scale. This study proposes an optimal operation strategy for a local multi‐vector energy storage system, which includes batteries, BH thermal storage, the power to the gas system and the fuel cell cars system. These storage systems can be divided into the short‐term storage system and inter‐seasonal storage system or low capacity storage system and high capacity storage system. The optimisation problem is divided into a two‐stage framework, (i) the first stage optimisation is seasonal optimisation, which gives an approximate optimal operation plan for BH heat storage systems in the following year; (ii) the second stage develops a day‐ahead robust optimal plan for all storage systems. Finally, the algorithm will return to seasonal optimisation to update the operation plan for BH heat storage systems to make results more accurate. The test case of eight nodes illustrates that the combined energy system of photovoltaic, heat pump power to gas, BH and batteries can provide hydrogen to fuel cell cars and significantly save power costs for customers with the optimal operation.